Application of Optimal Homotopy Asymptotic Method to Burger Equations. (16th July 2013) - Nawaz, R.; Ullah, H.; Islam, S.; Idrees, M.
Abstract : We apply optimal homotopy asymptotic method (OHAM) for finding approximate solutions of the Burger's-Huxley and Burger's-Fisher equations. The results obtained by proposed method are compared to those of Adomian decomposition method (ADM) (Ismail et al., (2004)). As a result it is concluded that the method is explicit, effective, and simple to use.